Comparando a eficácia da manta térmica com método de aquecimento passivo na prevenção de hipotermia - Morine, Renata Kimie [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Hypothermia is a common phenomenon in the perioperative period, and it affects 60 to 90% of patients submitted to anesthetic-surgical procedures. In order to minimize its incidence, warming methods are used. Such methods can be passive, such as orthopedic cotton, sheets and blankets, or active, such as warm-air blankets and thermal mattresses. In this scenario, the present study aimed at comparing two warming methods used in the intraoperative period. Patients submitted to abdominal surgery in the specialties of gynecology and gastric surgery from August to September 2010 were included in the study. After randomization, they were divided into two groups: one using a thermal blanket (group I) and one using orthopedic cotton (group II). At last, 9 patients were included. The variables for each question were considered according to occurrence frequency. Comparison between groups was performed by Student’s t test. With the purpose to analyze whether there was an association, the chi-square test or Fisher’s Exact test was used. Whenever it was applicable for multiple comparisons, Tukey’s test was utilized; p values < 0.05 were considered to be statistically significant for analysis. The sample comprised 6 males and 3 females submitted to gynecological and gastric surgeries. Their mean age was 48 years for group I and 46.2 years for group II. A predominance of general anesthesia was observed. The time of permanence in the operating room ranged from 80 to 360 minutes. With regard to warming parenteral solutions, the procedure was performed on 5 patients, and infusion of warm solution into the abdominal cavity was performed on 50% of the sample. Concerning the warming method used, 5 patients used a thermal blanket. In view of the results presented, it was not possible to conclude which warming method should be used due to sample size

A hipotermia é um fenômeno comum no perioperatório e que acomete de 60 a 90% dos pacientes submetidos ao procedimento anestésico-cirúrgico. Para minimizar a incidência são utilizados métodos de aquecimento que podem ser passivos como algodão ortopédico, lençóis e cobertores, e métodos ativos como manta de ar aquecido e colchão térmico. Diante deste contexto este estudo teve como objetivo comparar dois métodos de aquecimento utilizados no intra-operatorio. Foram incluídos os pacientes submetidos à cirurgia abdominal das especialidades de ginecologia e gastrocirurgia, no período de agosto a setembro de 2010. Estes foram divididos em dois grupos, com uso de manta térmica (grupo I) e com uso de algodão ortopédico (grupo II), após a randomização. Ao final, 9 pacientes formam incluídos. As variáveis de cada questão foram consideradas por freqüência de ocorrência. A comparação entre os grupos foi feita pelo teste t de Student. Com o objetivo de verificar se havia alguma associação, foi utilizado o teste qui-quadrado ou o teste exato de Fisher, quando aplicável para as comparações múltiplas foi utilizado o teste de Tukey. Considerou-se como estatisticamente significante para análise valores de p<0,05. A amostra foi constituída por 6 homens e 3 mulheres, submetidos a cirurgias ginecológicas e gastrocirurgia, com idade média de 48 anos para o grupo I e 46,2 anos para o grupo II ,e com predomínio de anestesia geral.Quanto ao tempo de permanência na sala de operação apresentou variação de 80 a 360 minutos. Em relação ao aquecimento das soluções parenterais o procedimento foi realizado com 5 pacientes. e também em 50% da amostra houve infusão de liquido aquecido na cavidade abdominal. Quanto ao método de aquecimento utilizado 5 pacientes utilizaram manta térmica. Em face dos resultados apresentados não foi possível concluir qual o melhor método... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Enfermagem medico-cirurgica; Hipotermia – Prevenção